Clinical trial of autologous adipose tissue-derived regenerative (stem) cells therapy for exploration of its safety and efficacy - Yoshio Sakai (Regenerative Therapy, 2021)
Introduction: Liver cirrhosis is the ultimate condition of chronic liver diseases. Non-alcoholic steatohepatitis and fatty liver diseases are emerging in association with metabolic syndrome largely due to excess nutrition. Stromal cells of adipose tissue are enriched mesenchymal stem cells which are pluripotent and immunomodulatory, which are expected to be applied for repairing/regenerative therapy of the impaired organs. Methods: We conducted the multi-institutional clinical trial (Japanese UMIN Clinical Trial Registry: UMIN000022601) of cell therapy using freshly isolated autologous adipose tissue-derived regenerative (stem) cells (ADRCs), which are obtained by the investigational trial device, adipose tissue dissociation device, for liver cirrhosis patients due to non-alcoholic steatohepatitis or fatty liver disease, to exploratory assess efficacy as well as safety of this trial. We completed treatment and 24 weeks follow-up for 7 patients. Results: We observed that 6 out of 7 patients' serum albumin concentration was improved. As for prothrombin activity, 5 out of 7 patients showed improvement. No trial-related adverse events, which were serious or non-serious, was observed. Besides, no malfunction of the investigational trial device was encountered. Conclusion: Thus, treatment with autologous ADRCs obtained with the investigational trial device in steatohepatitis-related cirrhosis was confirmed to be safely conductible and potentially promising for the retaining or improving the impaired hepatic reserve.